Determinan Dividend Payout Ratio - Laellatus Sarifah; Aida Nahar (Universitas Islam Nahdlatul Ulama Jepara, 2021)
The Dividend Payout Ratio is very important for shareholders in investment decisions. This study aims to analyze the factors affecting the DPR in companies indexed LQ45 for the period 2018-2019. The factors examined in this study are the CR, debt to equity ratio, return on assets, firm size, net profit margin, asset growth, sales growth, and earnings per share. This research examines companies with the LQ45 index that publish financial reports in rupiah currency during the 2018-2019 period. Based on www.idx.co,id data, there are 38 companies. This research used saturated sampling method and data analysis method employed multiple linear regression. The results of this study indicate that return on assets is the most dominant factor affecting the Dividend Payout Ratio in companies indexed LQ45. Meanwhile, CR, debt to equity ratio, firm size, net profit margin, asset growth, sales growth, and earnings per share have no effect on the DPR.